Lexical Occasional Units Expressing the Meaning of Action and State (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
the article discusses occasional units, document specific features, the study of the phenomenon of occasionalism in world and Russian linguistics, and lexical occasional units expressing the meaning of action and state using the example of the language of written sources of the national revival.